2012
DOI: 10.3390/e14061011
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Thermal Reservoirs

Abstract: Abstract:We explore the consequences of a deterministic microscopic thermostat-reservoir contact mechanism for hard disks where the collision rule at the boundary is modified. Numerical evidence and theoretical argument is given that suggests that an energy balance is achieved for a system of hard disks in contact with two reservoirs at equal temperatures. This system however produces entropy near the the system-reservoir boundaries and this entropy flows into the two reservoirs. Thus rather than producing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…By molecular dynamics, Morriss and co-workers studied [51] the low-density hard-disk system in a narrow linear channel, which is in contact with two thermostats of fixed "temperatures" on both ends [52]. In the model, hard disks collide with the thermostat walls according to deterministic rules [52][53][54]. The temperature profile, local entropy density, entropy production rate, and heat flux through the system were obtained [51].…”
Section: Computer Simulationsmentioning
confidence: 99%
“…By molecular dynamics, Morriss and co-workers studied [51] the low-density hard-disk system in a narrow linear channel, which is in contact with two thermostats of fixed "temperatures" on both ends [52]. In the model, hard disks collide with the thermostat walls according to deterministic rules [52][53][54]. The temperature profile, local entropy density, entropy production rate, and heat flux through the system were obtained [51].…”
Section: Computer Simulationsmentioning
confidence: 99%
“…As → 0 the system decouples from the reservoir and the boundary becomes a hard wall, and as → 1 the incoming momentum is replaced by the reservoir momentum. A recent study of this system in contact with two reservoirs of the same temperature [12] has shown that the active mechanical coupling leads to entropy production near each reservoir which then flows into the reservoir. These effects are local and involve a limited number of boundary layer particles regardless of the system size.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of this system in contact with two reservoirs of the same temperature [22,24,27] has shown that the active mechanical coupling leads to entropy production near each reservoir which then flows into the reservoir. These effects are local and involve a limited number of boundary layer particles regardless of the system size.…”
Section: The Modelmentioning
confidence: 99%